The unusual stoichiometry of ADP activation of the KATP channel - Hosy, Eric; Vivaudou, Michel (Frontiers in Physiology, 2014)
KATP channels, oligomers of 4 pore-forming Kir6.2 proteins and 4 sulfonylurea receptors (SUR), sense metabolism by monitoring both cytosolic ATP, which closes the channel by interacting with Kir6.2, and ADP, which opens it via SUR. SUR mutations that alter activation by ADP are a major cause of KATP channelopathies. We examined the mechanism of ADP activation by analysis of single-channel and macropatch recordings from Xenopus oocytes expressing various mixtures of wild-type SUR2A and an ADP-activation-defective mutant. Evaluation of the data by a binomial distribution model suggests that wild-type and mutant SURs freely co-assemble and that channel activation results from interaction of ADP with only 2 of 4 SURs. This finding explains the heterozygous nature of most KATP channelopathies linked to mutations altering ADP activation. It also suggests that the channel deviates from circular symmetry and could function as a dimer-of-dimers.